Review of Various Image Restoration and Denoising Methods Underwater Images (International Journal of Engineering and Computer Science, 2018)
The paper presents a denoising method, based on Daubechies Wavelet transform and filters, for underwater images. The method here adapts itself to various types of image noise as well as factor that are to be derived to estimate the noise-free coefficients. In the preference of the images in any field, a single parameter can be used to balance the preservation of relevant details against the degree of noise reduction. Edges play a important role in image representation, one effective means to enhance spatial resolution is to enhance the edges. DWT, a time-scale representation of the digital signal is obtained using digital filtering techniques. Effectiveness of this method is compared with all other techniques such as median ,wiener, bayes shrink and normal shrink methods for removing noise.This paper presents a review of some significant work in the area of denoising. We will introduce the wavelet and other filters methods with homomorphics filters multi-scale analysis framework and summarize related research work in this area.